Produção de tomateiro, híbrido momotaro, em função do estádio das mudas e da enxertia - Goto, Rumy [UNESP]; Sirtori, Luchele Furlan [UNESP]; Rodrigues, João Domingos [UNESP]; Lopes, Mario Cesar (Universidade Federal de Lavras (UFLA), 2010)
This work was carried out in a protected environment at São Paulo State University (UNESP) Sao Manuel Experimental Farm, College of Agronomical Sciences, Sao Manuel Municipality, São Paulo State, Brazil. The local soil was red-yellow sandy-phase latosol. The following development stages for transplanting were evaluated: seedlings presenting 5 to 6 definitive leaves, in full flowering and beginning of fruiting. Momotaro T-93 hybrid tomato (Lycopersicon esculentum Mill.) was grown on two rootstocks, the hybrids Anchor T and Kaguemusha, and in non-grafted ones. Evaluations included leaf area, seedling length, seedling dry matter at the moment of the transplant, total number of leaves per plant, fresh and dry matter of leaves below the third inflorescence, fruit classification according to diameter, and total fruit production until the eighth bunch. Non-grafted plants transplanted when they presented 5 to 6 definitive leaves had the highest mean fruit production and diameter. As regards grafted plants, no difference was detected concerning productivity and final quality when seedlings were in the stages from 5 to 6 definitive leaves until full flowering, and the rootstock Anchor T presented the best development.
Production of tomato, momotaro hibrid according to seedling stage and grafting
Keywords: Lycopersicon esculentum; protected cultivation; transplanting stages